2017
DOI: 10.3390/rel8110254
|View full text |Cite
|
Sign up to set email alerts
|

Spiritual/Religious Coping of Women with Breast Cancer

Abstract: This research aimed to evaluate the level of Spiritual/Religious Coping (SRC) of women with breast cancer. This is a quantitative, descriptive, cross-sectional study. A total of 94 mastectomized women who participated in the study were enrolled in a rehabilitation center of a higher education institution of São Paulo. Data were collected from October 2013 to June 2014 using a questionnaire with sociodemographic, clinical, and spiritual/religious data, stressor stimulus associated with breast cancer, and the SR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 17 publications
0
9
0
4
Order By: Relevance
“…The keys to coping strategies amongst Malay women are their religious beliefs and the context of their partnerships – that is, how much they value their relationships with their spouses similar to what had been experienced among women with breast cancer in other countries regardless their religions. 43 , 44 Those with strong religious beliefs are more likely to adapt to the difficult situation and to construe positive meanings out of negative experiences. 43 , 45 Relationship context contributes to the perceived severity of the illness: Women with appreciative, understanding husbands are more likely to resolve their difficulties and accommodate their husbands’ sexual needs, regardless of their own wishes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The keys to coping strategies amongst Malay women are their religious beliefs and the context of their partnerships – that is, how much they value their relationships with their spouses similar to what had been experienced among women with breast cancer in other countries regardless their religions. 43 , 44 Those with strong religious beliefs are more likely to adapt to the difficult situation and to construe positive meanings out of negative experiences. 43 , 45 Relationship context contributes to the perceived severity of the illness: Women with appreciative, understanding husbands are more likely to resolve their difficulties and accommodate their husbands’ sexual needs, regardless of their own wishes.…”
Section: Discussionmentioning
confidence: 99%
“… 43 , 44 Those with strong religious beliefs are more likely to adapt to the difficult situation and to construe positive meanings out of negative experiences. 43 , 45 Relationship context contributes to the perceived severity of the illness: Women with appreciative, understanding husbands are more likely to resolve their difficulties and accommodate their husbands’ sexual needs, regardless of their own wishes. On the other hand, those less considerate husbands are more likely to try to avoid sexual intimacy.…”
Section: Discussionmentioning
confidence: 99%
“…Both spirituality and religiosity are mechanisms to find meaning when faced with the illness process, which relates such phenomena to a source of support and hope (25)(26) . The cancer diagnosis often requires aggressive and painful therapies, resulting in undesirable side effects (27) .…”
Section: Discussionmentioning
confidence: 99%
“…Spirituality is important in regulating their emotions and considered as helpful in adjustment after cancer. Another study towards 94 women with mastectomized breast cancer showed that all respondents used spiritual/religious coping (SRC), mostly at high and very high level; SRC proved to be an important coping strategy in stress situations experienced by women with breast cancer and helpful in coping with the disease and the consequences of the treatments [36]. Similar study in women with cervical cancer is not found yet.…”
Section: Resultsmentioning
confidence: 97%